Everyday Nationalism and Authoritarian Rule: A Case Study of North Korea. Issue 6 (27th November 2020) - Dukalskis, Alexander; Lee, Junhyoung
Abstract: This article traces the evolution of "everyday nationalism" in North Korea and assesses its relationship to authoritarian resilience. It argues that coercion and the prospect of coercion play important roles in policing the contours of everyday nationalism. The state is able to infuse nationalism and authoritarian control into everyday life, but the "success" of its efforts has limits. This is due to social changes and the ways that material failures nurtured doubts about the legitimacy of the government among some citizens. It draws on data from North Korean state media, secondary historical literature, and 58 semi-structured interviews with North Koreans living in South Korea.